Um graffito do século XV-XVI no castelo de Montalegre - Barroca, Mário Jorge; Guedes, César (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2020)
Study of a graffiti identified in a tower of the castle of Montalegre, a fortification in the north of Portugal, built close to the Spanish border. The graffiti, representing a boat, occupies a large surface. An inscription, dated from 1580, related to the conclusion of works in the castle, suggests the chronology of the graffiti.